PERMAINAN TRADISIONAL DENGKAK UNTUK STIMULASI PENGEMBANGAN ANAK USIA DINI DI DESA SUKARAMAI KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Susanti, Eva; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2023)
This study aims to describe the traditional dengkak game in stimulating early childhood development in Sukaramai Village, Sungai Laur District, Ketapang Regency. The research method used is descriptive method with a qualitative research form. Sources of data in this study were the community, parents, PAUD teachers and children aged 5-6 years in Sukaramai Village, Sungai Laur District, Ketapang Regency. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study show that: 1. Dengkak traditional games in developing the potential of early childhood in the aspect of religious moral values there is the ability to behave well, get used to behaving well, sportsmanship, respect and honesty, accustom children to express gratitude, 2. Dengkak traditional games in development the potential of early childhood on the physical motoric aspect includes gross and fine motor skills, 3. Dengkak's traditional games develop the potential of early childhood on the cognitive aspect, there are learning and problem solving abilities, logical thinking, and symbolic thinking 4. Dengkak's traditional games develop potential of early childhood in the aspect of language there is the ability to understand language and express language, 5. Dengkak traditional games in developing early childhood potential in the social-emotional aspect there is the ability of self-awareness, a sense of responsibility for oneself and others, and prosocial behavior, 6. Dengkak traditional games in developing the potential of early childhood in the artistic aspects of the ability to draw various forms. Thus, the traditional dengkak game has the potential to develop aspects of early childhood in Sukaramai Village, Sungai Laur District, Ketapang Regency.